2011
DOI: 10.1007/978-3-642-24485-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Model-Driven Engineering and Optimizing Compilers: A Bridge Too Far?

Abstract: Abstract. A primary goal of Model Driven Engineering (MDE) is to reduce the cost and effort of developing complex software systems using techniques for transforming abstract views of software to concrete implementations. The rich set of tools that have been developed, especially the growing maturity of model transformation technologies, opens the possibility of applying MDE technologies to transformation-based problems in other domains. In this paper, we present our experience with using MDE technologies to bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These advantages are in fact the pillar principles of MDE and domain-specific modeling. Floch et al [31] observed many similarities between MDE and compilers research and principles. Thus, it is not surprising to see that many, though not exclusively, code generation tools came out of the MDE community.…”
Section: Code Generationmentioning
confidence: 99%
“…These advantages are in fact the pillar principles of MDE and domain-specific modeling. Floch et al [31] observed many similarities between MDE and compilers research and principles. Thus, it is not surprising to see that many, though not exclusively, code generation tools came out of the MDE community.…”
Section: Code Generationmentioning
confidence: 99%
“…These two research-oriented optimizing compiler infrastructures have faced the same software engineering issues during their development, and decided to use MDE to tackle them [46]. Indeed, compilers are composed of multiple passes manipulating several intermediate languages.…”
Section: A Uniform Model-driven Approach For Software and Language Enmentioning
confidence: 99%